Innovative Big Books: Revolutionizing Financial Literacy Education for Early Childhood Creativity - Husna, Nurul; Aini, Fadhilah Fadhilah; Nursobah, Asep (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2024)
The quality of a nation is greatly influenced by the level of literacy of its people, including financial literacy. Financial literacy education in early childhood is important to form wise financial habits. This research aims to design financial literacy media for early childhood through big book media innovations that are effective in increasing financial literacy understanding. This research uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Big book media is designed with colors, images, and simple questions to foster critical power, as well as using games as evaluations. The big book media developed and tested in 6 early childhood at TPK Raudhatul Quran Banda Aceh, shows the potential to be effective in improving children's understanding of financial literacy. This research contributes to creating innovative media to instill an understanding of financial literacy in early childhood which can be a reference for educators and future media development.